2010
DOI: 10.1111/j.1365-294x.2010.04685.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the marine macroalga Sargassum hemiphyllum (Phaeophyceae, Heterokontophyta) in northwestern Pacific

Abstract: Sargassum hemiphyllum is commonly found in Japan and Korea, with a variety, var. chinense, that is found distributed in the southern Chinese coast. We previously reported distinct genetic differentiation between the two taxa based on the PCR-RFLP data of plastid RubiscoL-S spacer. The present study aims at elucidating the phylogeographic pattern of S. hemiphyllum based on more markers in the nuclear and extranuclear genomes, with a view to reveal the occurrence of hybridization. The two allopatrically distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 72 publications
(164 reference statements)
8
67
1
Order By: Relevance
“…The disruption of the southward East China Sea Coastal Current due to the impact of the summer monsoon and discharge from the Yangtze River during the reproductive season of O. fasciatus may cause a disconnection between the Yellow Sea populations and the East China Sea populations (Dong et al 2012). Similar results of gene-flow disruption among populations by the Yangtze River were also reported in Chelon haematocheilus (Temminck & Schlegel, 1845), Sargassum hemiphyllum (Agardh), Cyclina sinensis (Gmelin, 1791) and Cellana toreuma (Reeve, 1854) along the continental slope of the Asian Pacific (Liu et al 2007;Zhao et al 2009;Cheang et al 2010;Dong et al 2012). Frequent gene flow was detected between the ZS and TW locations in the present study.…”
Section: Population Genetic Structure and Genealogical Structuresupporting
confidence: 60%
See 1 more Smart Citation
“…The disruption of the southward East China Sea Coastal Current due to the impact of the summer monsoon and discharge from the Yangtze River during the reproductive season of O. fasciatus may cause a disconnection between the Yellow Sea populations and the East China Sea populations (Dong et al 2012). Similar results of gene-flow disruption among populations by the Yangtze River were also reported in Chelon haematocheilus (Temminck & Schlegel, 1845), Sargassum hemiphyllum (Agardh), Cyclina sinensis (Gmelin, 1791) and Cellana toreuma (Reeve, 1854) along the continental slope of the Asian Pacific (Liu et al 2007;Zhao et al 2009;Cheang et al 2010;Dong et al 2012). Frequent gene flow was detected between the ZS and TW locations in the present study.…”
Section: Population Genetic Structure and Genealogical Structuresupporting
confidence: 60%
“…It has been reported that the Yangtze Delta was formed at least 3.2 million years ago based on the provenance of the sediment in the area of the modern delta (Jia et al 2010). AMOVA, F st and Φ pt analyses revealed limited gene exchange between the JN and ZS locations separated by the Yangtze River estuary, suggesting that the Yangtze River acted as a barrier to gene flow among populations on either side, which has also been observed in other marine species (Liu et al 2007;Zhao et al 2009;Cheang et al 2010;Dong et al 2012). According to the divergence time of the two stocks of O. fasciatus, we could conclude that it was at least 0.31-0.41 million years since the Yangtze River began to significantly influence the gene exchange among populations of O. fasciatus.…”
Section: Population Genetic Structure and Genealogical Structurementioning
confidence: 78%
“…Complete sequence of Cyt b gene, partial sequences of the 16S rRNA, D-loop and RAG-2 genes were obtained for all the sampled individuals. When direct sequencing of RAG-2 failed due to heterozygosity, amplicons of RAG-2 were cloned using a TA-cloning system (TakaRa Biotechnology, Dalian, China) following the manufacturer’s instructions [38]. The master mixture of polymerase chain reaction (PCR) contained approximately 100 ng of template DNA, 1 μL (10 pmol) of each primer, 5 μL of 10× reaction buffer, 2 μL of dNTPs (2.5 mM of each) and 2.0 U of Taq DNA polymerase, in a total volume of 50 μL.…”
Section: Methodsmentioning
confidence: 99%
“…This together with the Yangtze River discharge is assumed to form a contemporary dispersal barrier for marine species that require a hard substratum (e.g. intertidal rocky shore) or with larvae that cannot tolerant decreased salinity, including the gastropod Cellana toreuma [20], the bivalve Cyclina sinensis [34] and the macroalga Sargassum hemiphyllum [18, 35]. However, studies on other coastal fauna did not detect any genetic split across the Yangtze River [24].…”
Section: Introductionmentioning
confidence: 99%